WOMEN ENTREPRENEURSHIP IN PERIPHERAL FISHING AREA: ARE THEY REAL ENTREPRENEURS? - Muhammad, Nik Maheran Nik; Mustafa, Wan Zumusni Wan; Muin, Norhayati Abd. (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
The aim of the study is to investigate the decision making behaviour of the Malay women entrepreneurs at the peripheralÂ area of Tok Bali, Kelantan Malaysia. Six respondents were observed and interviewed using in depth interview protocol.Â The in depth interview (IDI) transcripts concluded that most respondents venture into business is just to raise theirÂ respective families and solve their current financial problem instead of contributing to the economy of the area. Thus,Â the characteristics of entrepreneurship among them do not exist. Therefore, most of the respondents cannot be categorizedÂ as real entrepreneurs as most of their businesses are just small-scale businesses to support their family. However, theyÂ do bring a significant change to their familyâs economy and play a role in changing their familyâs economic conditionÂ but do not act as catalyst for the economic change for the peripheral area. It was also found that the most popularÂ businesses in Tok Bali is âFish crackers (âi.e. Keropokâ)â business and they have received the governments assistanceÂ such as capital, machinery, business training and business premises. The present study is exploratory in nature, thus Â researchers will only able to describe the situation instead of recommending what should be done to improve theÂ situation. For further research, it is recommended that more extensive study to be done to gain more information onÂ their decision making behaviour towards entrepreneurship and their attribution to success. More respondents shouldÂ be interviewed to gauge more factors and issues. A mixed method with quantitative analysis will enrich the result.